KONSEP IDEAL HOTEL SYARI’AH SERTA PENERAPAN SYARI’AH HOTEL MUHAMMADIYAH A. MUIN SAIDI PADANG PANJANG - Mardalis, Mardalis; Asty, Wina (Ensiklopedia of Journal, 2025)
This study aims to describe how sharia principles are implemented in the management of the Muhammadiyah A. Muin Saidi Hotel in Padang Panjang, West Sumatra. By employing a descriptive qualitative method through interviews, observations, and document analysis, the research found that the hotel consistently applies sharia principles in its management, products, and services, in accordance with the fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) and Regulation No. 2 of 2014 by the Ministry of Tourism and Creative Economy. Policies such as the prohibition of non-mahram couples sharing a room, the provision of prayer facilities, and guarantees of halal food reflect the hotel’s strong commitment to Islamic teachings. This hotel serves not only as a place of accommodation but also as a platform for Islamic outreach (da’wah), promoting halal tourism and serving as a model of sharia hotel management in West Sumatra.Keywords: Sharia Hotel, Hotel Management, Halal Tourism